Clasificación de las provincias españolas según su tendencia ganadera 1950-1988 - Rubio Terrado, Pascual (Geographicalia, 2017)
Our contribution tries to establish a classification system of the Spanish provinces starting from the evolution shown in each of them through the census of the four major cattle species: bovine, ovine, caprine and porcine, from 1950 to 1988